Molecular Evolution and Association of Natural Variation in ZmARF31 with Low Phosphorus Tolerance in Maize - Wu, Fengkai; Liu, Zuoming; Xu, Jie; Gao, Shibin; Lin, Haijian; Liu, Ling; Liu, Yaxi; Lu, Yanli (Frontiers in Plant Science, 2016)
Low-phosphorus (P) stress is one of the major factors constraining plant growth and yield. Improving plant tolerance to P starvation through molecular breeding is an efficient alternative to increase grain production. In the study, 331 diverse maize inbreds were used to detect nucleotide diversity and favorable alleles of ZmARF31, which plays a key role in low P responses and root architecture regulation. Significant phenotypic variation was found in each of 11 tested traits under both P and no-P treatments, and 30 single nucleotide polymorphisms (SNPs) and 14 insertion-deletions (InDels) were detected in ZmARF31 among the 331 maize inbreds. The 5′-untranslated region (UTR) of ZmARF31 showed a small linkage disequilibrium (LD) block under significant purifying selection, whereas the 3′-UTR showed the most abundant diversity and a larger LD block. Thirty, fourteen, and nine natural variations were identified in ZmARF31 that were associated with P-deficiency-tolerance traits (P ≤ 0.01) by using the general linear model (GLM), GLM incorporated with population structure, and mixed linear model, respectively. Four SNPs were significantly associated with the total dry weight in the three models, of which SNPs S410 and S462 were located in a complete LD block. A further verification conducted in a recombinant inbred line population revealed that favorable allele G/G of nonsynonymous mutation S410 and favorable allele with a 38 bp insertion of InDel S1442 exhibited positive genetic effects on the total dry weight and total root tips, respectively. Expression analysis further confirmed that ZmARF31 was highly expressed in the roots of low-P-tolerant inbred 178. The protein encoded by ZmARF31 was located both in the nucleus and cytoplasm. Haplotypes carrying more favorable alleles showed a greater effect on phenotypic variation than single loci. Such haplotypes should be helpful to develop valuable genetic markers and perform maize molecular breeding.